The Association Between Perceived Discrimination and Allostatic Load in the Boston Puerto Rican Health Study. Issue 7 (September 2019) - Cuevas, Adolfo G.; Wang, Kaipeng; Williams, David R.; Mattei, Josiemer; Tucker, Katherine L.; Falcon, Luis M.
ABSTRACT: Objective: Perceived discrimination is a risk factor for poor health among ethnic and racial minority groups. However, few studies have examined the association between major lifetime and everyday perceived discrimination and allostatic load (AL), a preclinical indicator of disease. We examine the association between two measures of discrimination and AL among Puerto Rican adults. Methods: Using primarily wave 3 data from the longitudinal Boston Puerto Rican Health Study, we examined the association between major lifetime and everyday perceived discrimination and AL (multisystem dysregulation of 11 physiological components) among Puerto Rican adults residing in the Boston metro area ( N = 882). Five models were tested using multivariable regression. The final model adjusted for demographic factors, migration factors, socioeconomic status and work history, health behaviors/risk factors, and depressive symptom. Results: Respondents had a M (SD) AL score of 5.11 (1.76; range = 0–11). They had an average score of 0.21 (0.42) for major lifetime perceived discrimination (0–3) and 0.29 (0.49) for everyday perceived discrimination (0–3). In a fully adjusted model, major lifetime perceived discrimination was associated with greater AL ( b = 0.56; 95% CI = 0.19 to 0.92), whereas greater everyday perceived discrimination was marginally, but not significantly, associated with lower AL ( b = −0.42; 95% CI = −0.87 to 0.04). Conclusions: Perceived discrimination remains a common stressor and may be a determinant of AL for Puerto Ricans, although the type of perceived discrimination may have differing effects. Further research is needed to better understand the ways in which major lifetime and everyday perceived discrimination operate to effect physiological systems among Puerto Ricans.